2020
DOI: 10.1111/jfd.13198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pseudoloma neurophilia infection on the brain transcriptome in zebrafish (Danio rerio)

Abstract: Laboratory zebrafish are commonly infected with the intracellular, brain‐infecting microsporidian parasite Pseudoloma neurophilia. Chronic P. neurophilia infections induce inflammation in meninges, brain and spinal cord, and have been suggested to affect neural functions since parasite clusters reside inside neurons. However, underlying neural and immunological mechanisms associated with infection have not been explored. Utilizing RNA‐sequencing analysis, we found that P. neurophilia infection upregulated 175 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…21 Our results support other recent studies outlining the adverse effects of P. neurophilia infection on zebr afish. 2,13,15,21,22,24,28,29 The many potential unintended effects in infected fish argue for efforts toward the eradication of P. neurophilia in laboratory zebrafish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Our results support other recent studies outlining the adverse effects of P. neurophilia infection on zebr afish. 2,13,15,21,22,24,28,29 The many potential unintended effects in infected fish argue for efforts toward the eradication of P. neurophilia in laboratory zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…14 Naturally occurring clinical and subclinical infections in animals are well established to cause confounds and high variability that can lead to invalid or misinterpreted experiments and an accumulating body of experimental evidence has begun to characterize the adverse effects of P. neurophilia and other pathogens on zebrafish research. 2,13,15,21,22,24,28,29 However, subclinical PNI zebrafish often go undetected, and thus may be enrolled in, and potentially compromise, biomedical research projects. In addition, uninfected zebrafish may acquire the infection during the course of an experiment, potentially creating undesired effects on research outcomes.…”
mentioning
confidence: 99%
“…Further, transcriptomic approaches to better understand the immune responses will allow developing suitable diagnosis methods. Recently, Midttun et al (2020b) described that in P. neurophilia infected zebrafish no differentially expressed genes or enriched pathways were specific for nervous system functions but classical upregulation of immune-related cascades such as pro-inflammatory Th1 response was observed.…”
Section: Molecular Analysismentioning
confidence: 99%
“…The parasite also causes reduced fecundity (Ramsay et al., 2009). Moreover, this is a serious concern as a cause of non‐protocol‐induced variation in research because apparently healthy fish have been shown to have alterations in behaviour (Midttun, Vindas, Nadler, et al., 2020; Midttun, Vindas, Whatmore, et al., 2020; Spagnoli, Xue, & Kent, 2015; Spagnoli, Xue, Murray, et al., 2015) and in transcriptome profiles (Midttun, Vindas, Nadler, et al., 2020; Midttun, Vindas, Whatmore, et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…alterations in behaviour (Midttun, Vindas, Nadler, et al, 2020;Midttun, Vindas, Whatmore, et al, 2020;Spagnoli, Xue, Murray, et al, 2015) and in transcriptome profiles (Midttun, Vindas, Nadler, et al, 2020;Midttun, Vindas, Whatmore, et al, 2020).…”
mentioning
confidence: 99%